Effect of Cellulase and Protease Pretreatment on Dewaterability of Waste Activated Sludge from Paper Mill - Chaojun Wu; Kai Zhang; Jiachuan Chen; Shuping Li (BioResources, 2014)
The feasibility of cellulase and protease pretreatment to improve the dewaterability of waste activated sludge from papermaking (WASP) was evaluated. Dewatering properties such as capillary suction time (CST), dry solids content of the sludge cakes from the specific resistance of filtration (SRF), and compression were measured to quantify the effects of cellulase and protease in sludge dewatering. The changes in the amounts of proteins (PN) and polysaccharides (PS) in tightly bound extracellular polymeric substances (TB-EPS) was found to be the most important parameter with respect to sludge dewatering. Further study, through nitrogen adsorption, verified the large change in the average pore width and surface area. Therefore, the disruption of TB-EPS and the change in the inner structure of WASP granules are the fundamental reasons for the enhanced dewaterability.